Does Molluscum Contagiosum Need to be Managed Differently in Atopic Children? - Nicolas Andre; Adva Alyagon; Eman Jurban; Khen Moscovici; Amir Horev (Medical Journals Sweden, 2024)
The association between molluscum contagiosum and concomitant atopic dermatitis and its impact on clinical features and treatment outcomes remains unclear. This retrospective study, conducted in the paediatric dermatology clinic of a tertiary medical centre, aimed to compare molluscum patients with and without atopic dermatitis. A total of 615 children with molluscum were included, 13.17% of whom had atopic dermatitis. While the latter group exhibited higher lesion count and itchiness (p=0.026 and p=0.044, respectively), no significant differences were observed in average lesion diameter, ulceration, purulence, and erythema (p=0.239, p=0.730, p=0.682, and p=0.296, respectively). Both groups showed comparable responses to molluscum-specific and supportive treatments, with no distinct difference in outcomes or recurrence of visits. It was concluded that atopic dermatitis does not exacerbate molluscum morbidity, inflammation markers, treatment outcomes or recurrence rates.